Co-delivery of everolimus and vinorelbine via a tumor-targeted liposomal formulation inhibits tumor growth and metastasis in RCC - Pal K (Dove Medical Press, 2019)
Krishnendu Pal,* Vijay Sagar Madamsetty,* Shamit Kumar Dutta, Debabrata MukhopadhyayDepartment of Biochemistry and Molecular Biology, Mayo Clinic Florida, Jacksonville, FL 32224, USA*These authors contributed equally to this workBackground: Renal cell carcinoma (RCC) is notorious for its resistance towards chemotherapy and radiation therapy in general. Combination therapy is often helpful in alleviating the resistance mechanisms by targeting multiple signaling pathways but is usually more toxic than monotherapy. Co-encapsulation of multiple therapeutic agents in a tumor-targeted drug delivery platform is a promising strategy to mitigate these limitations.Methods: A tumor-targeted liposomal formulation was prepared using phospholipids, cholesterol, DSPE-(PEG)2000-OMe and a proprietary tumor-targeting-peptide (TTP)-conjugated lipopeptide. An efficient method was optimized to encapsulate everolimus and vinorelbine in this liposomal formulation. Single drug-loaded liposomes were also prepared for comparison. Finally, the drug-loaded liposomes were tested in vitro and in vivo in two different RCC cell lines.Results: The tumor-targeted liposomal formulation demonstrated excellent tumor-specific uptake. The dual drug-loaded liposomes exhibited significantly higher growth inhibition in vitro compared to the single drug-loaded liposomes in two different RCC cell lines. Similarly, the dual drug-loaded liposomes demonstrated significantly higher suppression of tumor growth compared to the single drug-loaded liposomes in two different subcutaneous RCC xenografts. In addition, the dual drug-loaded liposomes instigated significant reduction in lung metastasis in those experiments.Conclusion: Taken together, this study demonstrates that co-delivery of everolimus and vinorelbine with a tumor-targeted liposomal formulation is an effective approach to achieve improved therapeutic outcome in RCC.Keywords: liposomes, combination therapy, everolimus, vinorelbine, renal cancer, metastasis